Inflammation and Breast Density among Female Chinese Immigrants: Exploring Variations across Neighborhoods - Fang, Carolyn Y. (Cancer Causes Control, 2019)
PURPOSE: We examined associations of inflammation with breast density, a marker of breast cancer risk, among female Chinese immigrants and explored whether associations varied by neighborhood environment. METHODS: Assessments of serum C-reactive protein (CRP), soluble tumor necrosis factor receptor 2 (sTNFr2), and breast density were performed among 401 Chinese immigrants across the Philadelphia region. Participant addresses were geocoded, with the majority residing in areas representing traditional urban enclaves (i.e. Chinatown and South Philadelphia) or an emerging enclave with a smaller, but rapidly growing Chinese immigrant population (i.e., the Near Northeast). The remainder was classified as residing in non-enclaves. RESULTS: In multivariable adjusted regression models, CRP was inversely associated with dense breast area (p = 0.01). Levels of sTNFr2 were also inversely associated with dense breast area, but these associations varied by neighborhood (interaction p = 0.01); specifically, inverse associations were observed among women residing in the emerging enclave (p = 0.03), but not other neighborhoods. CONCLUSIONS: Among Chinese immigrant women, aggregate analyses that do not take neighborhood context into consideration can mask potential variations in association of inflammatory markers with breast density. Future studies should consider how neighborhood contextual factors may contribute to differential risk pathways.